Gene Conversion and the Evolution of Protocadherin Gene Cluster Diversity - Noonan, James P.; Grimwood, Jane; Schmutz, Jeremy; Dickson, Mark; Myers, Richard M. (Genome Research, 2004)
The synaptic cell adhesion molecules encoded by the protocadherin gene cluster are hypothesized to provide a molecular code involved in the generation of synaptic complexity in the developing brain. Variation in copy number and sequence content of protocadherin cluster genes among vertebrate species could reflect adaptive differences in protocadherin function. We have completed an analysis of zebrafish protocadherin cluster genes. Zebrafish have two unlinked protocadherin clusters, DrPcdh1 and DrPcdh2. Like mammalian protocadherin clusters, DrPcdh1 has both α and γ variable and constant region exons. A consensus protocadherin promoter motif sequence identified in mammals is also conserved in zebrafish. Few orthologous relationships, however, are apparent between zebrafish and mammalian protocadherin proteins. Here we show that protocadherin cluster genes in human, mouse, rat, and zebrafish are subject to striking gene conversion events. These events are restricted to regions of the coding sequence, particularly the coding sequences of ectodomain 6 and the cytoplasmic domain. Diversity among paralogs is restricted to particular ectodomains that are excluded from conversion events. Conversion events are also strongly correlated with an increase in third-position GC content. We propose that the combination of lineage-specific duplication, restricted gene conversion, and adaptive variation in diversified ectodomains drives vertebrate protocadherin cluster evolution.